2000
DOI: 10.1007/s100530050028
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing fragmentation of simple fluids with percolation theory

Abstract: We show that the size distributions of fragments created by high energy nuclear collisions are remarkably well reproduced within the framework of a parameter free percolation model. We discuss two possible scenarios to explain this agreement and suggest that percolation could be an universal mechanism to explain the fragmentation of simple fluids. PACS

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 27 publications
1
20
0
1
Order By: Relevance
“…Performing molecular dynamics calculations with a Lennard-Jones fluid, Campi and his collaborators (Campi et al, 2001a;Sator, 2000) have found that the cluster size distributions obtained with these three definitions are very similar. To quote Hill (1955): "A cluster is [.…”
Section: A Local Criterion: Hill Clustersmentioning
confidence: 99%
See 2 more Smart Citations
“…Performing molecular dynamics calculations with a Lennard-Jones fluid, Campi and his collaborators (Campi et al, 2001a;Sator, 2000) have found that the cluster size distributions obtained with these three definitions are very similar. To quote Hill (1955): "A cluster is [.…”
Section: A Local Criterion: Hill Clustersmentioning
confidence: 99%
“…It has to be noticed that the Hill's criterion can be used as well with Monte-Carlo calculations, although the velocities of the particles are not provided. Indeed, we checked by means of molecular dynamics simulations that mean cluster size distributions are not modified when we replace the velocity of each particle, provided by molecular dynamics simulations, with velocity components taken at random from a Gaussian distribution characterized by the temperature of the system (Sator, 2000). As far as mean cluster size distributions are concerned, position-velocity correlations are irrelevant and Monte-Carlo calculations can be used by allocating to each particle a velocity from a Gaussian distribution.…”
Section: A Local Criterion: Hill Clustersmentioning
confidence: 99%
See 1 more Smart Citation
“…Percolation models [255,256,257,258], the Fisher Droplet Model [221,226,259,260,261] and more recently the theory of universal fluctuations [207,225,262,263,264] have been employed to describe fragment size distributions and fluctuations and to tentatively derive information on the critical region of the liquid-gas transition: in finite systems the critical point becomes a critical region. The determinations of a scaling function and of a consistent set of critical exponents in different multifragmentation data also tend to support this hypothesis [97,141,265,266].…”
Section: Scaling and Fluctuations For Fragment Sizesmentioning
confidence: 99%
“…Fragmentation is a widely studied phenomena [1] with applications ranging from conventional fracture of solids [2] and collision induced fragmentation in atomic nuclei/aggregates [3] to seemingly unrelated fields such as disordered systems [4] and geology [5]. In this paper we consider a problem where an object of initial size (or length) x is first broken into m random pieces of sizes x i = r i x with m i=1 r i = 1 provided the initial size x > x 0 where x 0 is a fixed 'atomic' threshold.…”
mentioning
confidence: 99%